Participación y trabajo en equipo entre los jóvenes de la junta vecinal de seguridad ciudadana Líderes por un Milagro Seguro del Centro Poblado El Milagro, Trujillo, 2021 - Cordova Santamaria, Diana Yanira (2022)
The present investigation was carried out with the purpose of analyzing the influence of participation in teamwork among the members of the Neighborhood Board of Citizen Security Leaders for a Safe Miracle. The sample consisted of 41 members whose ages ranged between 18 and 31 years, in the development of the present investigation three methods were applied, which were the inductive-deductive, the analytical - synthetic and the statistical; as well as the use of research techniques such as the interview and the survey that were presented through the interview guide instruments, interview record and questionnaire which allowed obtaining quantitative and qualitative data allowing the understanding of the indicators and your variables. According to the results obtained in the investigation, it is shown that participation negatively influences the teamwork of the Líderes por un Milagro Seguro neighborhood council, evidencing that 32% never attend face-to-face meetings, 29% almost never demonstrates responsibility, 69% do not have the availability of time to participate, this is because the members of the neighborhood board of citizen security are studying and/or working.